Implementasi Pembelajaran Berdiferensiasi Berbasis Digital dalam Menganalisis Struktur dan Kebahasaan Teks Prosedur - Tamsiruddin Tamsiruddin (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2024)
The implementation of differentiated learning is a new insight into realizing learning that is centered on student needs. However, teachers are still confused about implementing it in learning. This research aims to describe the implementation of digital-based differentiated learning in analyzing the structure and language of procedural texts. This research attempts to describe in detail the forms and responses of students to the implementation of digital-based differentiated learning. The method used in this research is the descriptive method. The data in this research were obtained from observations of the learning process, initial learning test, questionnaires filled out by students via google form, and interviews with class VII.3 students at State Middle School 1 Parepare after participating in the lesson. The results of the data analysis show that the implementation of digital-based differentiated learning can be applied to learning to analyze the structure and language of procedural texts. One way that can be done is to integrate digital-based differentiated learning with the quantum learning learning model. Through this implementation, students assess that learning to analyze the structure and language of procedural texts is fun, so they are more enthusiastic about learning. Apart from that, students consider that the implementation of digital-based differentiated learning is worth continuing.